STUDENT PERSONALITY OF BROKEN HOME VICTIMS AT SDN BANJAREJO, MADIUN CITY - Husnun Fitria Rasyidah (Universitas Tadulako, 2020)
This study aims to determine the impact of broken home on the personality of elementary school students. This research was conducted in the eighth semester at SDN Banjarejo, Madiun City. This research uses a case study qualitative research. This research instrument uses observation sheets and interviews. using aspects of the big five personality are the neuroticsm, extravertion, oppenness, agreeableness and conscientiousness. The results show that students who have broken home have a tendency to the low level of operational aspects in the field of learning but are also supported in the aspect of extravertion and agreeableness on the first indicator shows a high level. This shows that in socializing with others and their peers do not experience difficulties and do not withdraw in their social environment.